Polish-language Threads in Lithuanian Healing Conjurations (Zagovory) - Vologdina, Tatjana (Vilnius University Open Series, 2021)
Lithuanian conjurations (zagovory) constitute a unique part of Lithuanian folklore. In the collection of conjurations’ manuscripts described in the publication of Daiva Vaitkevičienė (2008), we will find records of these archaic texts in various languages, including Polish. Polish-language conjurations constitute a separate subgroup in the Balto-Slavic context. Following the chronological criterion, we are dealing with texts of pre-Christian and after-Christ origins. Due to mutual cultural influences as well as functioning of different languages within Lithuania, it is usually not possible to determine the original language of conjuration. Only in a few cases we are able to state, which version of conjuration is its translation. This is indicated primarily by the structure of the text as well as its lexical features, adaptation or transliteration. The article presents an attempt to compare Polish and Lithuanian texts, identify and analyze Polish language threads, their motives and subject matter as well as the ways in which such conjurations function.